Pemanfaatan Limbah Udang (Litopenaeus vannamei) Dengan Penambahan Ekstrak Kunyit (Curcuma domestica) Dalam Pembuatan Kaldu Bubuk - Saman, Widya Rahmawaty; Lapamona, Oktaningsih (Jambura Fish Processing Journal, 2024)
Most of the shrimp waste generated by shrimp processing activities come from the head, skin, and tail. Shrimp skin contains protein (25% - 40%), chitin (15% - 20%), and calcium carbonate (45% - 50%). Additionally, shrimp meat is a good source of minerals, especially calcium, phosphorus, potassium, and zinc. The amount of shrimp waste remains a problem that needs to be addressed for utilization efforts. This research aims to determine the influence of different concentrations of turmeric extract on the broth powder of shrimp waste. Shrimp waste can be an alternative ingredient to replace seasoning additives in cooking. The study was designed using a Completely Randomized Design with one factor, namely the concentration of turmeric extract. The research was conducted with one control and three treatments. The test parameters conducted included solubility testing, water content testing, and antioxidant testing. Based on the results obtained, the highest solubility value was found in broth powder without the addition of turmeric extract, which was 25.0%. The highest water content was found in shrimp waste broth powder with the addition of 15% turmeric extract, which was 61.44%, and the strongest antioxidant was found in shrimp waste broth powder with the addition of 15% turmeric extract, which was 46.44 ppm.